2019
DOI: 10.1007/s11910-019-0952-9
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing and Idiopathic Normal-Pressure Hydrocephalus: Recent Pathophysiological Advances

Abstract: Purpose of Review Idiopathic normal-pressure hydrocephalus (iNPH) is characterized clinically by ventriculomegaly, abnormal gait, falls, incontinence, and cognitive decline. This article reviews recent advances in the pathophysiology of iNPH concerning sleep-disordered breathing (SDB) and glymphatic circulation during deep sleep. Recent Findings The authors found iNPH frequently associated with obstructive sleep apnea (OSA). A critical factor in iNPH is intracranial ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 93 publications
0
39
0
Order By: Relevance
“…Thirdly, sleep disorders are frequently diagnosed among iNPH patients. A study among 31 iNPH subjects revealed that all iNPH patients suffered from sleep abnormality to different extent 95 . Over 90.3% of iNPH patients had an obstructive sleep apnea 95 .…”
Section: Glymphatic Impairment Increases Brain Damage In Inphmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirdly, sleep disorders are frequently diagnosed among iNPH patients. A study among 31 iNPH subjects revealed that all iNPH patients suffered from sleep abnormality to different extent 95 . Over 90.3% of iNPH patients had an obstructive sleep apnea 95 .…”
Section: Glymphatic Impairment Increases Brain Damage In Inphmentioning
confidence: 99%
“…A study among 31 iNPH subjects revealed that all iNPH patients suffered from sleep abnormality to different extent 95 . Over 90.3% of iNPH patients had an obstructive sleep apnea 95 . Sleep abnormality could promote the overnight accumulation of metabolites in the interstitial space.…”
Section: Glymphatic Impairment Increases Brain Damage In Inphmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results don't back up this finding, but it must be noted that our questionnaire represents only the time close to the diagnosis and not their alcohol consumption earlier in life. Also, a frequent association between iNPH and obstructive sleep apnea has been found [45]. Our analysis with the probable fNPH families showed no differences in the prevalence of sleep apnea between the groups (Table 3).…”
Section: Alcohol Sleep Apnea Sfmbt1 and Apoe ε4mentioning
confidence: 51%
“…There is evidence that the glymphatic system dysfunction could affect the development of iNPH [ 41 43 ]. It has been suggested that in iNPH the glymphatic system is possibly impaired through neuroinflammation, reactive astrogliosis, depolarization and reduced density of aquaporin-4 (AQP4) and sleep disturbances, which could reduce the normal clearance of CSF [ 43 45 ]. Interestingly in rat models, diabetes has been found to cause glymphatic system dysfunction, reduction in AQP4 density, neuroinflammation, microvascular damage, blood–brain barrier damage and cognitive decline that could be associated with glymphatic system dysfunction [ 46 49 ].…”
Section: Discussionmentioning
confidence: 99%